2010
DOI: 10.1038/msb.2010.98
|View full text |Cite
|
Sign up to set email alerts
|

Evolution, genomic analysis, and reconstruction of isobutanol tolerance in Escherichia coli

Abstract: Escherichia coli has been engineered to produce isobutanol, with titers reaching greater than the toxicity level. However, the specific effects of isobutanol on the cell have never been fully understood. Here, we aim to identify genotype–phenotype relationships in isobutanol response. An isobutanol-tolerant mutant was isolated with serial transfers. Using whole-genome sequencing followed by gene repair and knockout, we identified five mutations (acrA, gatY, tnaA, yhbJ, and marCRAB) that were primarily responsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
240
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 256 publications
(250 citation statements)
references
References 46 publications
9
240
1
Order By: Relevance
“…In this study, increased ethanol tolerance was not linked to higher ethanol yields (SI Appendix, Fig. S6), which is in keeping with a recent study that examined Escherichia coli isobutanol tolerance and productivity (13).…”
Section: Nonrandom Distribution Of Mutations Across the Genome And Theirsupporting
confidence: 91%
“…In this study, increased ethanol tolerance was not linked to higher ethanol yields (SI Appendix, Fig. S6), which is in keeping with a recent study that examined Escherichia coli isobutanol tolerance and productivity (13).…”
Section: Nonrandom Distribution Of Mutations Across the Genome And Theirsupporting
confidence: 91%
“…However, it still faces some challenges, such as ameliorating the toxic effects of intermediates and products of interest (Keasling, 2010). Numerous studies have focused on increasing the tolerance of different production strains toward various biochemicals using different strategies (Alper, Moxley, Nevoigt, Fink, & Stephanopoulos, 2006; Atsumi et al, 2010; Dunlop et al, 2011; Goodarzi et al, 2010). An alternative to this approach is to identify alternative production hosts that are naturally tolerant to higher concentrations of the chemicals of interest.…”
Section: Introductionmentioning
confidence: 99%
“…12 Thus, the isobutanol-induced growth arrest limits the overall productivity for an industrial scale application. To overcome isobutanol toxicity, Atsumi et al 13 recently isolated an isobutanol-tolerant E. coli strain by a sequential transfer method. However, the final strain was more tolerant to isobutanol, but showed much lower isobutanol formation, when compared with the parental strain E. coli JCL260/pSA55/pSA69.…”
Section: Discussionmentioning
confidence: 99%
“…However, the final strain was more tolerant to isobutanol, but showed much lower isobutanol formation, when compared with the parental strain E. coli JCL260/pSA55/pSA69. 13 More recently, Minty et al used experimental evolution combined with genome resequencing to identify the genotypic adaptations of E. coli lineages with increased isobutanol tolerance. Thereby, the authors identified a set of mutations (marC, hfq, mdh, acrAB, gatYZABCD, rph) common in several isobutanol tolerant lineages and they speculated that rpoS and post-transcriptional regulators such as hfq are promising targets to improve isobutanol production with E. coli.…”
Section: Discussionmentioning
confidence: 99%